Stress and Its Impact on Mental and Physical Health (Journal Of Educational and Psychological Researches, 2022)
Stress is an inevitable part of life. Stress occurs when stressful events of self, environmental, or social origin affect the individual's resilience and threaten to collapse his psychological and physical systems. The stress represents difficulties and obstacles that may exceed the individual's ability to bear them and deal with them, which causes him stress and causes negative effects on his psychological and physical health. Therefore, the current research aimed to identify the negative effects of psychological stress on the psychological and physical health of the individual through the literature that dealt with this topic. It was among the results of the research that one of the negative effects of stresses on mental health is the deterioration of the concept of the self in individuals and their feeling of frustration and poor compatibility and the emergence of symptoms of various mental disorders they have. While the negative effects of stress on the physical health of individuals are weakening the work of the immune system and infection with various infections, in addition to high blood pressure, cardiovascular disease, diabetes, digestive diseases and skin diseases. The researcher recommended to educate the community about stress and its impact on the health of individuals, and to prepare awareness programs by professionals on this topic.